PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS DENGAN KEPUASAN DAN KEPERCAYAAN SEBAGAI VARIABEL INTERVENING (Pada PT. Federal International Finance cabang Palu) - Paluwati, Lisna; Bachri, Syamsul; Ponirin, Ponirin (Katalogis, 2018)
The aim of the study are: 1) to determine and anylize the influence of service quality on clients’ satisfaction at PT. FIF, Palu; 2) to determine and analyze the influence of service quality on trust of clients at PT. FIF, Palu; 3) to determine and analyze the influence of clients’ of service quality on clients’ loyalty at PT. FIF, Palu; 4) to determine and analyze the influence of satisfaction on clients’ trust at PT. FIF, Palu; 5) to determine and analyze the influence of clients’ satisfaction on loyalty of clients’ at PT. FIF, Palu; 6) to determine and analyze the influence of trust on clients’ loyalty at PT. FIF, Palu. Sample consist of 156 peoplewho are selected by accidental sampling. Tool of analyze is Structural Equation Modelling (SEM) for hypotesist test. The result finds that: 1) service quality has positive and significant influence of clients’satisfaction at PT. FIF, Palu; 2) service quality has positive and significant influence of clients’trust at PT. FIF, Palu; 3) service quality has positive and significant influence of clients’ loyalty at PT. FIF, Palu; 4) clients’ satisfaction has positive and significant influence of clients’trust at PT. FIF, Palu;5) clients’ satisfaction has positive and significant influence of clients’ loyalty at PT. FIF, Palu; 6) clients’ trust has positive and significant influence of clients’ loyalty at PT. FIF, Palu;